Pre-service teachers’ noticing: On the way to expert target - Vondrová, Naďa; Novotná, Magdalena; Pavlasová, Lenka; Robová, Jarmila; Stará, Jana; Uličná, Klára (Scientia in educatione, 2023)
Unlike prevailing research focusing on what pre-service teachers attend to in a lesson and how they interpret it, the study investigates the content of their comments, knowledge-based reasoning and whether it agrees with experts’ views. Study 1 determined the dimensions of quality teaching pertinent to lessons in which a new subject matter is introduced and made a noticing target. In Study 2, pre-service teachers (n = 174) at the end of their university study made a written reflection of a video lesson, which was compared against the target. Most could not discern situations important for deep work with the content in the lesson. They failed to apply their theoretical knowledge in their interpretation of the ones they mentioned. Only half of their comments included knowledge-based reasoning, and their views were mostly partially consistent or inconsistent with the experts’ ones. This highlights the need to focus on content-related important situations in a lesson and their interpretation in teacher preparation and on developing the ability to discern the dimensions of instructional quality in concrete lessons.